Classification of Students' Performance in Computer Programming Course According to Learning Style - Norwawi, NM; Abdusalam, SF; Hibadullah, CF; Shuaibu, BM (IEEE Computer Soc, 2024)
In Information Technology related programs, computer programming courses are made compulsory subjects in most institutions of learning. However there are many reports on poor performance among students in such courses. Previous studies examined some of the variables influencing students' performance using statistical data analysis. The critical point of this study is the use of classification algorithm to extract patterns which are examined from the cognitive factor specific learning style. The findings show that that student's good performance in programming courses has a visual, active and sequential learning style.